2020
DOI: 10.1002/ajhb.23542
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight and body composition in 6‐to‐8 years old Maya children

Abstract: Objective: To test the hypothesis that fetal growth, indexed by birth weight (BW), induce metabolic adjustments in the fetus that will be reflected in differences in body composition in a sample of 6-to 8-years old urban Maya children from Yucatan, Mexico. Methods: We measured height (cm), weight (kg) and triceps skinfold (mm) in 260 children (boys: 132, girls: 128), and height (cm) and weight (kg) in their mothers. Body composition was estimated in children through bioelectrical impedance analysis. Outcome va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…body composition during childhood (Azcorra et al, 2016;Azcorra et al, 2021;Azcorra & Méndez, 2018;Osorno-Covarrubias et al, 2002;Varela-Silva et al, 2009). We hope to stimulate future studies aimed at analyzing the link between size at birth and phenotype, and functional characteristics and illnesses during childhood, adolescence, and adulthood by using these references as a methodological tool that allow situating any sample from Yucatan in the context of the population this belong.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…body composition during childhood (Azcorra et al, 2016;Azcorra et al, 2021;Azcorra & Méndez, 2018;Osorno-Covarrubias et al, 2002;Varela-Silva et al, 2009). We hope to stimulate future studies aimed at analyzing the link between size at birth and phenotype, and functional characteristics and illnesses during childhood, adolescence, and adulthood by using these references as a methodological tool that allow situating any sample from Yucatan in the context of the population this belong.…”
Section: Discussionmentioning
confidence: 99%
“…Since the references we produced derive from a population‐based dataset over 5‐year period, these can be used by researchers to compare their samples and answer a wide range of research questions about variability in growth and phenotype at birth. Few studies have analyzed the birthweight in Yucatec population and its relationship with maternal characteristics, neonatal mortality, and body composition during childhood (Azcorra et al, 2016 ; Azcorra et al, 2021 ; Azcorra & Méndez, 2018 ; Osorno‐Covarrubias et al, 2002 ; Varela‐Silva et al, 2009 ). We hope to stimulate future studies aimed at analyzing the link between size at birth and phenotype, and functional characteristics and illnesses during childhood, adolescence, and adulthood by using these references as a methodological tool that allow situating any sample from Yucatan in the context of the population this belong.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in South Africa (infants aged 24 months) reported positive associations between weight gain and fat mass, fat-free mass, fat mass index, and fat-free mass index with no difference between genders ( 57 ). In Mexico, a study of Maya children (mean age 7.5 years) indicated that birth weight was positively associated with fat-free mass index and fat mass index among males only ( 58 ). A study of Brazilian adults (aged 35–74 years) found that low birth weight predicted higher levels of truncal fat in females but not in males ( 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Yucatecan Maya show the shortest heights in the global adult population as a result of chronic undernutrition during childhood. Also, birth weight has been positively associated with fat and fat-free mass in Maya children at 6-8 years of age (56). The phenotypic characteristics acquired early in development appear to be transmitted intergenerationally through epigenetic processes.…”
Section: Early Development and Intergenerational Influences Shaping T...mentioning
confidence: 94%